Group Guidance Using Problem Based Learning To Improve Student Career Planning (Literasi Nusantara, 2023)
The purpose of this research is motivated by the presence of students who have anxiety in planning a career to continue to high school. Efforts made in improving student career planning is with group guidance using a problem based learning model. This research is a classroom action research, which consists of 30 class XI students who will be given treatment and compared with the percentages of the career planning questionnaire between pre-cycle and after-cycle. The results of the study in cycle I the percentage in career planning was 67.8 in the low category and increased in cycle II to 80.8 in the high category. The results of the study show that group guidance services using the problem-based learning model are effective in improving student career planning.